Heart rate recovery after maximal and submaximal exercise - Karjalainen, Pasi (2012)
Pasi Karjalainen (2012). Heart rate recovery after maximal and submaximal exercise. Department of Biology of Physical Activity, University of Jyväskylä, Master thesis in exercise physiology, 76 pages. Heart rate recovery (HRR) after exercise reflects autonomic control of the heart. Heart rate recovery (HRR) has shown to have prognostic value among asymptomatic populations and patients with diseases. In addition, changes in HRR may reflect the effects of training load. The role of parasympathetic reactivation in decrease of heart rate (HR) is known to be strong immediately after the cessation of exercise. It is also shown that HRR is affected by the activity of the sympathetic system that is highly accelerated as a result of strenuous physical activity. Higher exercise intensity and longer exercise duration increases cumulation of various metabolic products and catecholamines, which slows down the decrease in sympathetic activity to the heart during recovery. The aim of this study was to examine the association between HRR after maximal and different intensities of submaximal exercises. In addition, it was examined whether HRR was associated with body composition (body mass, body mass index, skinfold thickness), maximal oxygen consumption (VO2max), and running performance (maximal running speed during the last minute of exercise). The subjects (n=10), a group of healthy physically active men, performed graded maximal exercise on a treadmill and a set of sub¬maximal exercises (with grade length of one minute). For submaximal exercises, the target heart rate in graded exercise was defined respectively as 90 % (SUB-90), 80 % (SUB-80) and 70 % (SUB-70) of maximal HR. Heart rate information was measured after exercise in standing (P-STANDING) or sitting position (P-SITTING). P-STANDING included a maximal exercise and the sub-maximal exercises SUB-90, SUB-80 and SUB-70. In P-SITTING, a maximal exercise and SUB-80 only were included. Correlation between maximal and sub¬maximal exercise during recovery period was examined as based on R-R interval (RRI) length. During 60-sec recovery period, higher positive correlation in RRI length (ms) was observed at the higher submaximal exercise intensities (r≥0.82, p<0.01 relating to the SUB-90, r≥0.71, p<0.05 relating to the SUB-80). HRR was faster after SUB-80 than after maximal exercise in the sitting position up to the 45-sec time point (44 ± 9 vs. 35 ± 5 bpm, p<0.05), but not in standing position after similar exercise (34 ± 11 vs. 30 ± 7 bpm, p=n.s.). Higher decrease of HR during the first 60 seconds of recovery (HRR60s) was associated with better running performance both in standing and sitting positions. Instead, an association between HRR60s and VO2max (ml·min-1·kg-1, l·min-1) or body composition was not observed. In conclusion, correlation of RRI length during recovery between maximal and sub-maximal exercises was higher when the submaximal exercise intensity was higher and it was also higher in standing than in the sitting position. Body position had negligible effect to HRR during the first 30-sec period during recovery after maximal exercise. After submaximal exercise HRR was faster than after maximal exercise in sitting position, but not in standing position after similar exercise. Keywords: heart rate recovery, autonomic regulation of heart rate, exercise intensity